2003
DOI: 10.1111/j.1349-7006.2003.tb01358.x
|View full text |Cite
|
Sign up to set email alerts
|

Evodiamine, a constituent of Evodiae Fructus, induces anti‐proliferating effects in tumor cells

Abstract: he dried, unripe fruit of Evodiae Fructus (Evodia rutaecarpa Benth., Rutaceae) is known as "Goshuyu" in Japanese. In traditional Chinese medicine, it has long been utilized for the treatment of headache, thoracicoabdominal pain, vomiting, cold and reduced blood circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 43 publications
3
85
0
1
Order By: Relevance
“…2). These results are in line with previous reports that evodiamine-induced cell death is associated with apoptosis in different cancer cell types such as breast (8), thyroid (9), liver (10), prostate (11-14), leukemic T-lymphocyte (5,15), melanoma (6,(16)(17)(18), cervical (19,20), colon (21)(22)(23)(24), colorectal (25) and lung cancer cells (26).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…2). These results are in line with previous reports that evodiamine-induced cell death is associated with apoptosis in different cancer cell types such as breast (8), thyroid (9), liver (10), prostate (11-14), leukemic T-lymphocyte (5,15), melanoma (6,(16)(17)(18), cervical (19,20), colon (21)(22)(23)(24), colorectal (25) and lung cancer cells (26).…”
Section: Resultssupporting
confidence: 92%
“…Evodiamine is a naturally occurring quinolone alkaloid found in the fruit of Evodia rutaecarpa. The data of several studies concerning its cytotoxic activity in cancer cells demonstrated that evodiamine inhibited the growth of a wide variety of tumor cells, including breast (8), thyroid (9), liver (10), prostate (11)(12)(13)(14), leukemic T-lymphocyte (5,15), melanoma (6,(16)(17)(18) cervical (19,20), colon (21)(22)(23)(24), colorectal (25) and lung cells (26) through induction of apoptosis, regulation of cell cycle and reduction of invasion and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…9A), has a different three-dimensional structure than evodiamine, and cannot inhibit cell proliferation or invasion (6,9). We investigated whether rutaecarpine affects NF-B activation.…”
Section: Evodiamine Represses Tnf-induced Nf-b-dependent Genementioning
confidence: 99%
“…Evodiamine 1 (see Fig. 1) has recently been shown to suppress the proliferation of a wide variety of tumor cells, including prostate cancer cells (4), leukemic T-lymphocytes (5), monocytic leukemia cells (6), melanoma cells (6,7), cervical cancer cells (6), and mouse fibrosarcoma cells (6), but it apparently has no toxic effects against normal peripheral blood mononuclear cells (6). 1 The abbreviations used and trivial name are: evodiamine, 8,13,13b14-tetrahydro-14-methlindolo[2Ј3Ј: 3,4]pyrido [2,1-b]quinazolin-5-[7H]-one; NF-B, nuclear factor-B; IB, inhibitory subunit of NF-B; IKK, IB␣ kinase; TNF, tumor necrosis factor; TNFR, TNF receptor; TRADD, TNFR-associated death domain; NIK, NF-B-inducing kinase; IL, interleukin; SEAP, secretory alkaline phosphatase; PMA, phorbol 12-myristate 13-acetate; TUNEL, terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick end-labeling; IAP, inhibitor-of-apoptosis protein; XIAP, X chromosome-linked IAP; FLIP, Fas-associated death domain protein-like IL-1␤-converting enzyme-inhibitory protein; COX, cyclooxygenase; MMP, matrix metalloproteinase; TRAF, TNF receptor-associated factor, PBS, phosphate-buffered saline; ICAM, intercellular adhesion molecule; MDR, multidrug resistance protein; NO, nitric oxide; FBS, fetal bovine serum; JNK, c-Jun NH 2 -terminal kinase; MAPK, mitogen-activated protein kinase; PARP, poly(ADP-ribose) polymerase; EMSA, electrophoretic mobility shift assay; GST, glutathione S-transferase; MTT, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide.…”
mentioning
confidence: 99%
“…Evodiamine (evo) is a quinazolinocarboline alkaloid extracted from the fruit of Wu-Zhu-Yu (Evodiae fructus; Evodia rutaecarpa Benth, Rutaceae), which has been used in traditional Chinese medicine for the treatment of gastrointestinal disorders, headache and hypertension. [23][24][25] It has recently been reported that evo exerts antiobesity effects through the stimulation of an extracellular signal-regulated kinase/mitogen-activated protein kinase pathway. 26 Therefore, it was interesting to assess the effects of evo alone and in combination with rosi on adipocyte differentiation in vitro and obesity related to diabetes in vivo.…”
Section: -13mentioning
confidence: 99%